Analisis Pemilihan Pemasok Cat pada UKM SBS Garage and Paint - Tambunan, Juniansyah; Loyda Tarigan, Elsya Paskaria (Fakultas Teknik UMRI, 2024)
UKM SBS Garage and Paint is a workshop that operates in the field of motorbike and car body repaint services. The observation results show that this SME does not yet have the right supplier to become a supplier of epoxy paint and clear coat paint. The aim of this research is to determine the best supplier using the Analytical Hierarchy Process (AHP) method combined with the Expert Choice application. This method refers to the concept of pairwise comparisons that exist in a hierarchical structure. The criteria used in selecting suppliers include: Quality, Delivery, Responsibility and Flexibility. The research results show that the main priority in selecting a supplier is the Quality criterion with a weight of 0.517 in the AHP calculation while the Expert Choice has a weight of 0.525. The supplier that is the first priority in the AHP and Expert Choice calculation results is Triwana Color Center, second is the Daya Warna Paint Shop and the supplier that is third is U-pol Indonesia